Chorea Hyperglycemia Basal Ganglia Syndrome in a 63-Year-Old Male - Michael Sperling; Roshan Bhowansingh (Case Reports in Medicine)
Chorea hyperglycemia basal ganglia syndrome (CHBG) is a rare condition that manifests within the setting of uncontrolled nonketotic diabetes mellitus. The objective of this case report is to present a patient found to have CHBG and provide a timeline in terms of his workup and subsequent treatment. We also present a commentary on the current understanding of the pathophysiology and treatment and how this was applied to our patient. The case involves a 63-year-old poorly controlled diabetic male who presented with a one-week history of uncontrolled choreiform movements of his left upper extremity. His initial glucose level was 339 mg/dl. HbA1C was 9.9%. CT scan of the head demonstrated an abnormal increased intensity within the right lenticular nucleus and right caudate head most likely due to microcalcifications/mineralization. MRI of the brain demonstrated nonspecific T1 and T2 hyperintense abnormalities in the same area about the right basal ganglia. These findings were consistent with the movement pattern he was displaying and with a diagnosis of CHBG. Gradual control of his blood sugar levels over 48 hours led to resolution of his choreiform symptoms. After better medication adherence as an outpatient, endocrinology follow-up 6 months after discharge found his HbA1C drop to a level of 7.1%. There was no recurrence of his symptoms. CHBG is a rare manifestation of poorly controlled diabetes but is the one that clinicians should be aware of. Early recognition and gradual treatment of elevated blood glucose levels appear to lead to total resolution of choreiform symptoms.